The scientific production about communication in the Brazilian journal Interface - Cyrino, Antonio Pithon [UNESP] (2020)
Introduction: Considering the importance of the Brazilian journal Interface among the Collective Health journals and as a space of production of knowledge and practices in the area in Latin America, this work aimed at mapping the scientific production related to communication in its various dimensions throughout the magazine's 20 years of existence (1997 to 2017). Methodology: This is a descriptive study of the quantitative and qualitative aspects of production on communication through content analysis. Results: During this period, the journal published 1,343 manuscripts among which 154 were related to communication, representing 11.47% of all papers. Empirical studies were predominant (52.6%), followed by theoretical studies (25.97%). The identified thematic fields were: Media (26.62%); Collective Health (26.62%); Professional education (16.88%); Professional relationship, patient/family/service (14.29%); Information and Communication Technologies (9.09%); and Communication and society (1.3%). Conclusion: This thematic diversity demonstrates the Communication and Health field's wealth and heterogeneity of topics. However, the low number of publications related to communication highlights the lack of scientific production on this matter in Collective Health.